Seleção genômica e estudo de associação em um rebanho experimental da raça Nelore - Silva, Rafael Medeiros Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The growing global demand for safe and sustainable food production has motived a restructuring in the beef production sector aiming the production of better quality products without increasing the productive cost. Animal feeding is the most important economic component of beef production systems. Due the conventional processing of cattle carcasses refrigeration after slaughter, an adequate quality carcass must have enough fat covering to guarantee its preservation and desirable quality for consume. Selection for feed efficiency has not been effective mainly due to difficult and high costs to obtain the phenotypes. The application of genomic selection using single nucleotide polymorphisms (SNPs) can decrease the cost of animal evaluation as well as the generation interval. However, there is no consensus among researches about the best methodology to obtain genomic prediction for each trait. The objective of this study was to compare methods of genomic evaluation using high-density SNP panel (BovineHD BeadChip - Illumina) for feed efficiency traits and to identify genomic regions associated to carcass traits in a small beef cattle population. After quality control, a total of 437,197 SNP genotypes were available for 761 Nelore animals from Institute of Animal Science, Sertãozinho, SP, Brazil. The data set contained 896 records for efficiency traits, such as residual feed intake (RFI), feed conversion ratio (FCR), average daily gain (ADG), and dry matter intake (DMI), 2,306 ultrasound records for longissimus muscle area (LMA), 1,832 for backfat thickness (BF), and 1,830 for rump fat thickness (RF). Methods of analysis were traditional BLUP, single step genomic BLUP (ssGBLUP), genomic BLUP (GBLUP), a Bayesian regression method (BayesCπ) and single-step genome-wide association (ssGWAS). Average accuracies ranged from 0.10 to 0.58 using BLUP, from 0.09 to 0.48 using GBLUP, from 0.06 to 0.49 using BayesCπ and from 0.22 to 0.49 using ...

A crescente demanda por produção alimentar sustentável tem motivado uma re-estruturação no setor de produção de carne objetivando a obter produtos de melhor qualidade sem aumentar os custos de produção. Alimentação animal é o componente econômico mais importante dos sistemas de produção de carne bovina. Devido ao tradicional processo de refrigeração após o abate, se faz necessário uma adequada cobertura de gordura na carcaça para garantir a sua preservação e qualidade desejável para consumo. A seleção para eficiência alimentar não tem sido eficaz, principalmente devido aos custos elevados e dificuldade para obter os fenótipos. A aplicação da seleção genômica utilizando polimorfismos de nucleotídeo único (SNPs) pode diminuir o custo de avaliação animal, bem como o intervalo de geração. No entanto, ainda não há consenso entre os pesquisadores sobre a melhor metodologia para a obtenção predição genômica para cada característica. O objetivo deste estudo foi comparar métodos de avaliação genômica usando o painel de marcadores do tipo SNP de alta densidade (BovineHD BeadChip - Illumina) para eficiência alimentar e identificar regiões genômicas associadas à características de carcaça em uma pequena população de bovinos de corte. Após o controle de qualidade, um total de 437197 genótipos ficou disponível para 761 animais da raça Nelore do Instituto de Zootecnia, Sertãozinho, SP, Brasil. O conjunto de dados continha 896 informações fenotípicas para as características de eficiência, como a consumo residual de alimentar (CAR), taxa de conversão alimentar (TCA), ganho em peso médio diário (GMD), e consumo de matéria seca (CMS), 2.306 informações de ultrassom para a área de olho de lombo (AOL ), 1832 para a espessura de gordura na região lombar (EGL), e 1830 para a espessura de gordura na região da garupa (EGG). Os métodos analisados foram: BLUP tradicional, single step...
Keywords: Bovino de corte - Carcaças; Eficiencia alimentar; Polimorfismo (Genetica); Genômica; Genetica animal; Genomics